2018
DOI: 10.3233/hsm-17182
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement, fairness and trust: An empirical assessment

Abstract: This article investigates the role that trust plays in moderating the relation between employee engagement and fairness, in service enterprises. The study's purposefulness was to examine, first, the link between employee engagement and fairness and, second, whether trust -often treated as a dependent or an intermediate construct-moderates the relation between these two constructs. By utilizing both cross-sectional and quantitative-data collection methods, a questionnaire survey allowed collecting data from 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…A conceptual framework links the key constructs to each other and provides a base for emerging empirically testable hypotheses. The current paper extends prior research (Rhoades and Eisenberger, 2002;Baran et al, 2012;Salanova et al, 2003;Schaufeli and Bakker, 2004;Schaufeli et al, 2002;Biswas et al, 2013;Abbas and Wu, 2018;Nikolova et al, 2019) in several ways. More specifically, current research tried to reveal a knowledge understanding of work engagement in three ways.…”
Section: Discussionsupporting
confidence: 86%
“…A conceptual framework links the key constructs to each other and provides a base for emerging empirically testable hypotheses. The current paper extends prior research (Rhoades and Eisenberger, 2002;Baran et al, 2012;Salanova et al, 2003;Schaufeli and Bakker, 2004;Schaufeli et al, 2002;Biswas et al, 2013;Abbas and Wu, 2018;Nikolova et al, 2019) in several ways. More specifically, current research tried to reveal a knowledge understanding of work engagement in three ways.…”
Section: Discussionsupporting
confidence: 86%
“…Employees engagement is an important aspect is safety management. Thus, important findings on this behaviour dimension were presented through the study of the role that trust plays in moderating the relation between employee engagement and fairness, in service enterprises in [19] and by [20] where research findings demonstrate the importance of workplace well-being in promoting work engagement.…”
Section: Considerations On Responsibility In Ohs Management Systemsmentioning
confidence: 99%
“…Trust has been taken as moderator in various studies. Trust moderates the link among employee engagement and justice for service enterprises (Abbas & Wu, 2018). It is indicated that trust in manager moderates the relationship of perceived HRM practices with employee prosperity, employee intention to quit and task execution (Alfes et al, 2013).…”
Section: Trust In Management As Moderatormentioning
confidence: 99%